IOT GATEWAY MENGGUNAKAN PROTOKOL MQTT PADA PERANGKAT KENDALI BERBASIS MODBUS-RTU - Imadudin Harjanto (Jurnal Ilmiah Teknosains, 2020)
One of the main goal of IoT implementation is to integrate existing device to the global information and communication infrastructure. Nowadays, most of new product have been designated to be IoT ready with, some feature to easily integrated to the internet world. The challenging is how to integrate old existing devices which doesn’t support new communication protocol. One of example is Autonics TK4S, a temperature monitoring controller based on Modbus RTU serial line communication which is very usual in industry. This paper discussed the scenario how to implement IoT to the device with Modbus RTU communication protocol to integrate with global internet while still maintaining the Modbus and MQTT character: lightweight and flexibility. Next thing to discuss is the security problem in Modbus. After some examination, we get result that security can be implemented by adding authentication. Meanwhile, the lightweight and flexibility still can be maintained.  In our scenario, latency of the system is still low at less than 0,3 s for Modbus-MQTT broker-client communication and less than 0,01 s for the MQTT communication alone. Data rate is still can be maintained at less than 9kbps.